The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s20010093
|View full text |Cite
|
Sign up to set email alerts
|

An Autonomous Fruit and Vegetable Harvester with a Low-Cost Gripper Using a 3D Sensor

Abstract: Reliable and robust systems to detect and harvest fruits and vegetables in unstructured environments are crucial for harvesting robots. In this paper, we propose an autonomous system that harvests most types of crops with peduncles. A geometric approach is first applied to obtain the cutting points of the peduncle based on the fruit bounding box, for which we have adapted the model of the state-of-the-art object detector named Mask Region-based Convolutional Neural Network (Mask R-CNN). We designed a novel gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Such tasks require robust algorithms to the unforeseen variations of these variables. In [ 26 , 27 ], a stereo kinematic method is used to compensate for parallax errors.…”
Section: Methodsmentioning
confidence: 99%
“…Such tasks require robust algorithms to the unforeseen variations of these variables. In [ 26 , 27 ], a stereo kinematic method is used to compensate for parallax errors.…”
Section: Methodsmentioning
confidence: 99%
“…The autonomous rice harvester with a combined robot performed harvesting, unloading and restarting with adequate accuracy [49]. The autonomous harvesting grippers with machine vision locate target like peduncles for various crops and remove the leaves and stems as obstacles to improve the harvesting system [50]. A manipulator (Jaco arm) can perform trimming of a bush into three shapes and the navigation system tracked the generalized travelling salesman problem (GTSP) [51].…”
Section: Unmanned Ground Vehicles (Ugvs)mentioning
confidence: 99%
“…Davis et al [36] presented the construction of a pneumatic end effector dedicated to handling delicate sliced fruits and vegetables. Zhang et al [37] conducted operational tests in real conditions of a robot equipped with a finger gripper connected to the cutting device, intended for harvesting strawberries concluded that it is necessary to properly cultivate plants and select varieties with a regular shape of the fruit.…”
Section: Related Work Connected With the End-effectormentioning
confidence: 99%